Formulasi dan Uji Evaluasi Sediaan Sirup Ekstrak Etanol Daun Salam (Syzygium polyanthum) - Pratiwi, Nindia Ayu; Endrawati - Politeknik Kesehatan Bhakti Mulia, Susi (IJMS - Indonesian Journal on Medical Science, 2021)
Abstract : Bay leaves are one of the traditional plants that can be used as medicine. Bay leaves have chemical contents, including essential oils, flavonoids, saponins, and tannins. These flavonoid compounds can reduce uric acid levels in the blood. This study aims to formulate the ethanol extract of bay leaves in syrup preparation and to determine whether the syrup meets the evaluation test. This type of research is an experimental study by evaluating the syrup preparations in formulas 1, 2 and 3 that have been made. The tests carried out included: organoleptic test, pH test, homogeneity test, specific gravity test, viscosity test, and volume removed test. The results can be analyzed statistically using the One Way Anova SPSS 22.0 test for windows. The organoleptic results of the syrup formulation of the ethanol extract of bay leaves are liquid, brownish green in color, smell of orange essence, sweet taste, have a pH 7 and homogenity. The specific gravity of formulas 1, 2, and 3, respectively, is 1.2011 g / ml; 1.2056 g / ml; 1.2064 g / ml. The viscosities of formulas 1, 2, and 3 are 1.86494 cps, respectively; 1.87008 cps; 1,87063 cps. ANOVA test shows a significance value (<0.001) <(0.05) so that there are differences in specific gravity and viscosity between formulas. The ethanol extract of bay leaves can be formulated into syrup preparations and based on the results of evaluation tests including organoleptic, pH, homogeneity, specific gravity, viscosity, and volume removed from the three formulations meet the requirements for the evaluation test for syrup preparations.Keywords: bay leaf, syrup, evaluation testAbstrak : Daun salam merupakan salah satu tanaman tradisional yang dapat dimanfaatkan sebagai obat. Daun salam mempunyai kandungan kimia antara lain minyak atsiri, flavonoid, saponin, dan tanin. Senyawa flavonoid tersebut yang dapat menurunkan kadar asam urat didalam darah. Penelitian ini bertujuan untuk memformulasikan ekstrak etanol daun salam dalam sediaan sirup dan mengetahui sediaan sirup memenuhi uji evaluasi. Jenis penelitian ini merupakan penelitian eksperimental yaitu dengan melakukan uji evaluasi sediaan sirup pada formula 1, 2 dan 3 yang telah dibuat. Uji yang dilakukan meliputi: uji organoleptis, uji pH, uji homogenitas, uji bobot jenis, uji viskositas, dan uji volume terpindahkan. Hasil yang di dapat dianalisis secara statistik menggunakan uji One Way Anova SPSS 22.0 for windows. Hasil organoleptis sediaan sirup ekstrak etanol daun salam berbentuk cair, warna hijau kecoklatan, bau essen jeruk, rasanya manis, memiliki rata-rata pH 7 dan homogen. Bobot jenis formula 1, 2, dan 3 berturut-turut yaitu 1,2011 g/ml ; 1,2056 g/ml ; 1,2064 g/ml. Viskositas formula 1, 2, dan 3 berturut-turut yaitu 1,86494 cps ; 1,87008 cps ; 1,87063 cps. Uji ANOVA menunjukkan nilai signifikansi (< 0,001) < (0,05) sehingga ada perbedaan bobot jenis dan viskositas antar formula. Ekstrak etanol daun salam dapat diformulasikan menjadi sediaan sirup dan berdasarkan hasil uji evaluasi yang meliputi organoleptis, pH, homogenitas, bobot jenis, viskositas, dan volume terpindahkan dari ketiga formulasi memenuhi syarat uji evaluasi sediaan sirup.Kata kunci : daun salam, sirup, uji evaluasi